What's mine is yours : the rise of collaborative consumption - Botsman, Rachel; Rogers, Roo. (New York : Harper Business, 2010)
'An idea-fueled book that explores the rise of new economic models based on shared resources and collective consumption--and the first articulation of a major socioeconomic phenomenon'--
Includes bibliographical references and index.
Keywords: Consumption (Economics); Resource allocation; Cooperation